GLOBAL REGULAR SOLUTION FOR THE EINSTEIN-MAXWELL-BOLTZMANN-SCALAR FIELD SYSTEM IN A BIANCHI TYPE-I SPACE-TIME - Norbert, Noutchegueme (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
We prove an existence and uniqueness of regular solution to the Einstein-Maxwell-Boltzmann-Scalar Field system with pseudo-tensor of pressure and the cosmological constant globaly in time. We clarify the choice of the function spaces and we establish step by step all the essential energy estimations leading to the global existence theorem.